The experience of critical self-reflection by life coaches: a phenomenological study. Issue 2 (3rd July 2019) - Shaw, Lynn; Glowacki-Dudka, Michelle
ABSTRACT: Life coaches benefitted from learning opportunities that increase their coaching effectiveness. Utilising critical self-reflection activities, life coaches created a continuing professional development opportunity to heighten awareness of the impact of self on life coaching. This qualitative phenomenological study addressed the gap in understanding the experience of critical self-reflection for five certified life coaches. Data were collected through the use of adapted critical incident questionnaires, journaling and semi-structured interviews. Five themes emerged: (a) supportive structure and discipline, (b) increased self-awareness, (c) renewed passion, (d) tools for professional development and (e) enhanced relationships with self and others. Critical self-reflection provided introspective self-analysis to enhance their coaching skills, to increase their energy for coaching sessions and to create a deeper connection with their clients. The coaches recommended that critical self-reflection be taught in professional development trainings.